2012
DOI: 10.1557/opl.2012.1437
|View full text |Cite
|
Sign up to set email alerts
|

Electron Self-trapping in Ge2 Se3 and its Role in Ag and Sn Incorporation

Abstract: We present a set of density functional theory (DFT) calculations on the electronic structure of Ag and Sn in Ge 2 Se 3 in a periodic model. We show that electron self-trapping is a persistent feature in the presence of many defects. Ag and Sn autoionize upon entering Ge 2 Se 3 becoming Ag + and Sn 2+, respectively, and the freed electrons self trap at the lowest energy site. Both Ag and Sn can substitute for Ge, and we present formation energies as a function of Fermi level that show that Sn can substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This first operation generates Sn ions from the SnSe layer and forces them into the active Ge2Se3 layer [24][25][26]. Theoretical calculations predict that these Sn ions facilitate the incorporation of Ag into the active layer at the Ge-Ge bonding sites [27]. This occurs through an energetically favorable process in which the electrons entering the active layer from the negative bottom electrode, concurrently with the formation of Sn ions near the positive top electrode, enable formation of a pair of self-trapped electrons in the Ge2Se3 active layer strongly localized around the Ge-Ge dimers present in this Ge-rich glass [28].…”
Section: Device Operationmentioning
confidence: 99%
“…This first operation generates Sn ions from the SnSe layer and forces them into the active Ge2Se3 layer [24][25][26]. Theoretical calculations predict that these Sn ions facilitate the incorporation of Ag into the active layer at the Ge-Ge bonding sites [27]. This occurs through an energetically favorable process in which the electrons entering the active layer from the negative bottom electrode, concurrently with the formation of Sn ions near the positive top electrode, enable formation of a pair of self-trapped electrons in the Ge2Se3 active layer strongly localized around the Ge-Ge dimers present in this Ge-rich glass [28].…”
Section: Device Operationmentioning
confidence: 99%
“…These values for ion density essentially assume that all (or almost all) the metal in the electrolyte is available to contribute to the ion current which may be a point of contention (especially in the case of Cu). However, switching models support these values and density functional theory (DFT) simulation has strongly suggested that Ag auto-ionizes in chalcogenide glasses, leading to very high ion concentration [97]. Using the above values, we see that for an electric field of 10 6 V cm −1 (1 V across a 10 nm thick electrolyte), the current density in these systems differs by around seven orders of magnitude (1.9×10 4 A cm −2 for the high case versus 1.3×10 −3 A cm −2 for the low case) but increasing the field narrows the differential.…”
Section: Sample Calculations For Ion Transportmentioning
confidence: 99%
“…Further density functional theory calculations show that Ag and Sn will autoionize upon entering the Ge 2 Se 3 , becoming Ag + and Sn 2+ [44]. The freed electrons self-trap at the lowest energy site.…”
Section: Figure 94 Ge 2 Se 3 Epr Spectra At 300 and 77 K Under Dark mentioning
confidence: 96%